2019
DOI: 10.1088/1361-6463/ab36d4
|View full text |Cite
|
Sign up to set email alerts
|

Cold plasma-based control of the activation of pancreatic adenocarcinoma cells

Abstract: Cold atmospheric plasma (CAP) has shown strong anti-cancer capability in vitro and in vivo. The interaction between CAP and cancer cells build the foundation to understand the anticancer effect of a direct CAP treatment. The CAP-based activation phenomenon is a key factor to understand the CAP cancer treatment. The CAP-treated pancreatic adenocarcinoma cells instantaneously entered a specific activation state, in which these cancer cells become very sensitive to the cytotoxicity of both reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The basic operating parameters of CAP source can be manipulated to obtain different levels of cellular activation following direct CAP treatment. 115 Parameters such as the flow rate of the carrying gas (Helium), the discharge voltage, and the discharge frequency each had an impact on the activation of pancreatic cancer cells. It was found that the greatest impact on cell activation was seen with alteration of the discharge voltage.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…The basic operating parameters of CAP source can be manipulated to obtain different levels of cellular activation following direct CAP treatment. 115 Parameters such as the flow rate of the carrying gas (Helium), the discharge voltage, and the discharge frequency each had an impact on the activation of pancreatic cancer cells. It was found that the greatest impact on cell activation was seen with alteration of the discharge voltage.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…On one hand, the strong micromolecular cells-based H 2 O 2 generation has been observed in directly CAP-treated cancer cells [ 168 , 169 , 170 ]. On the other hand, directly CAP-treated cancer cells enter the activation state and become very sensitive to the cytotoxicity of long-lived reactive species like H 2 O 2 and NO 2 - [ 171 , 172 ]. These two cellular responses do not appear in indirect CAP treatment [ 173 ].…”
Section: Cross-species Similaritiesmentioning
confidence: 99%
“…In that case, pancreatic cancer cells were sensitized to the cytotoxicity of long-lived reactive species, such as H 2 O 2 and NO 2 − . [148,149] The activation mechanism is also unknown. However, the short-lived reactive species and physical factors rather than long-lived reactive species may cause the activation in direct treatment.…”
Section: The Selectivity Based On Physical Factorsmentioning
confidence: 99%